Gambaran Trombositosis Terhadap Penyakit Jantung Koroner pada Penderita Diabetes Melitus: Thrombocytosis Profile in Relation to Coronary Heart Disease among Patients with Diabetes Melitus - Dairista Istna Syelviana; Suyanto; Mohammad Arifin Noor (Jurnal Keperawatan Berbudaya Sehat, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease that contributes to the increased incidence of coronary heart disease (CHD). Chronic hyperglycemia can trigger a prothrombotic state and hematological abnormalities such as thrombocytosis. This study aimed to describe the thrombocytosis profile in DM patients based on the occurrence of CHD. This was a descriptive retrospective study using medical records of 160 DM patients at Sultan Agung Islamic Hospital, Semarang. Platelet counts were classified according to WHO and CDC clinical reference values. Data were analyzed using univariate analysis. The results showed that the majority of respondents had normal platelet counts (63.8%), but there was a significant proportion of thrombocytosis at 28.7% (46 patients). Among patients with CHD (29 patients), the occurrence of thrombocytosis was found to be 11.9% (19 patients), while in the non-CHD group, it was 16.9% (27 patients). In conclusion, thrombocytosis is a hematological finding frequently observed in DM patients and is important to consider in clinical evaluation for cardiovascular risk stratification.